Editorial: Anti-Trafficking Education: Sites of care, knowledge, and power - Fukushima, Annie Isabel; Hill, Annie; Suchland, Jennifer (Anti-Trafficking Review, 2021)
This article introduces a Special Issue on anti-trafficking education. The past decade has seen a dramatic increase in the sites for anti-trafficking education and the range of educators who shape how the public and institutions understand and respond to human trafficking. Thus, there is a need to analyse the formalised and informalised practices that facilitate teaching and learning about trafficking. We argue that anti-trafficking education can perpetuate misinformation and myths about trafficking as well as legitimise carceral systems that lead to dehumanisation and violence. At the same time, critical approaches to teaching trafficking can encourage and inform endeavours to create structural change, social justice, and individual empowerment. We conclude that if the expansion of anti-trafficking education is divorced from longstanding movements for equity, then it runs the risk of teaching about trafficking while upholding practices and systems of oppression, exclusion, and expropriation, as well as diverting attention and resources from global work toward social and structural change.